PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW DALAM UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA: Penelitian Tindakan Kelas Pada Siswa Kelas X Perhotelan 2 SMK Negeri 1 Tasikmalaya - Siska, Nelia (LPPM Universitas Bina Bangsa, 2022)
The aim of this research is to improve student learning outcomes in trigonometry material in class X Hospitality 2 SMK Negeri 1 Tasikmalaya. The method used in this research is the classroom action research method. The data collection techniques used are observation techniques and written test techniques. The population and sample in this study were 35 students of Class X Hospitality 2. Based on the results of data analysis, it was found that student learning outcomes in trigonometry concepts in class at the beginning of cycle I was 32.80, the final test score was 75.80 and in cycle II the final test score was 81.40. This research concludes that the use of the jigsaw type cooperative learning model can improve the mathematics learning outcomes of trigonometry concepts in class X Hospitality 2 students at SMK Negeri 1 Tasikmalaya